Different Harmonic Characteristics Were Found at Each Location on TCM Radial Pulse Diagnosis by Spectrum Analysis. (5th July 2018) - Tsai, Yun-Ning; Huang, Yi-Chia; Lin, Sunny Jui-Shan; Lee, Shen-Ming; Cheng, Yung-Yen; Chang, Yu-Hsin; Su, Yi-Chang
Abstract : Purpose . This study aimed to clarify whether it is appropriate to choose any measurement location for pulse diagnosis research. Methods . A total of 37 subjects were recruited and measured for pulse pressure waves at 18 locations (9 per hand of "three positions and nine indicators"). These data were Fourier-transformed to the frequency spectrum, and the harmonics of C0-C10 of each location were obtained. Box plots of the harmonics were generated using SPSS v.22.0 and R v.3.4.1. Data were compared with multivariate analysis of variance (MANOVA) with a randomized block design. Results . The results showed that certain harmonics were different at different positions and different indicators; the harmonics of the same indicator at different positions (except for C8 and C10) and those of different indicators for the same position (except for C4 and C5) were significantly different (p<0.05). Conclusions . In future researches of pulse diagnosis, due to the significant differences between positions and indicators, it is recommended that the measurement position should be carefully chosen instead of choosing any measurement location to ensure the integrity of the acquired information for further analyzing physiological or pathological status.